Systematic review of the effects of excessive occlusal mechanical load on the periodontum of rats - Brandini, Daniela [UNESP]; Debortoli, Caio [UNESP]; Felipe Akabane, Sara [UNESP]; Poi, Wilson [UNESP]; Amaral, Marina [UNESP] (Wolters Kluwer, 2018)
Objective: This study aims to systematically evaluate the effects of traumatic occlusion on the periodontal tissue of rats. The set of questions to be answered were-Can traumatic occlusion acting on a healthy and an unhealthy periodontium cause periodontal destruction? Design: The protocols for systematic review were all developed, following the Preferred Reporting Items for Systematic reviews and Meta-Analyses statement and applied to animal research. Reporting of In vivo experiment guidelines for reporting animal research to assess the risk of bias of the studies. Materials and Methods: A literature search was conducted using MEDLINE through PubMed and manual search from the reference lists of main articles related to the theme. Results: This search strategy identified 65 references, of which 33 were considered inappropriate. The full texts of 32 articles were read, 31 of which did not meet the eligibility criteria and were excluded. The final selection included 1 article for which data was extracted for further evaluation. The article included shows a strongest reaction in the periodontium in front of a secondary occlusal trauma as inflammation and apical migration of the junctional epithelium, bone degradation, and decrease in the quantity of collagen fiber. However, primary occlusal trauma also presents these alterations, with the exception of apical migration of the junctional epithelium. Conclusions: Although only one study was included in the systematic review of traumatic occlusion, there is some evidence from experimental studies on animals that shows a coherent picture of the effects of traumatic occlusion on the periodontium. However, new studies are needed to fully answer the questions posed by this systematic review.
Keywords: Alveolar bone; animal models; occlusion; periodontal ligament; systematic review